2013
DOI: 10.1002/j.1532-2149.2013.00412.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensory hyperinnervation and increase in NGF, TRPV1 and P2X3 expression in the epidermis following cast immobilization in rats

Abstract: The time course of the increase in peripheral nerve fibres and in the expression of TRPV1 and P2X3 paralleled the development of hypersensitivity, which suggests that histological changes of the skin following cast immobilization may have some relation to the resulting hypersensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 67 publications
3
20
1
Order By: Relevance
“…We found that NGF level and peripheral nerve fiber density increased in the gastrocnemius muscle during cast immobilization. These results are similar to those in our previous study showing that NGF expression in the keratinocytes and peripheral nerve fibers increased in immobilized skin . We assume that the increase in NGF level and peripheral nerve fiber density are related to the mechanisms underlying immobilization‐induced muscle pain.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We found that NGF level and peripheral nerve fiber density increased in the gastrocnemius muscle during cast immobilization. These results are similar to those in our previous study showing that NGF expression in the keratinocytes and peripheral nerve fibers increased in immobilized skin . We assume that the increase in NGF level and peripheral nerve fiber density are related to the mechanisms underlying immobilization‐induced muscle pain.…”
Section: Discussionsupporting
confidence: 92%
“…We found that the PPT of the gastrocnemius muscle in the IM group significantly decreased unilaterally at 2 weeks after immobilization, and this decrease continued up to 4 weeks after immobilization. This PPT change in the skeletal muscle was almost the same as that seen in the skin using von Frey filament during cast immobilization in previous studies . However, because we measured the PPT of the skeletal muscle using the Randall‐Selitto apparatus through the skin, skin hyperalgesia may have also contributed in the IM group.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The percentage of single-labeled neurons over total neurons and that of double-labeled over classical neuronal markers (NF200, CGRP or IB4)-IR neurons were calculated from 4–5 sections obtained from the L 4 or L 5 DRG. The cross-sectional area of TRPV1-positive neurons in DRGs, as well as optical density (OD) of TRPV1 immunoreactivity in DRGs, SDHs, epidermal and dermis (the area 0–50 µm below the dermo-epidermal junction, method see [26]) were measured using the free NIH software ‘Image J’v1.46r.…”
Section: Methodsmentioning
confidence: 99%
“…P2X3 and P2X2/P2X3 double knockout mice display reduced nocifensive responses to ATP and formalin injection, as well as bladder hyporeflexia (Cockayne et al, 2000(Cockayne et al, , 2005, and both dorsal root and nodose ganglia neurons lose sensitivity to the selective agonist α,β-methylene ATP (α,β-meATP; Zhong et al, 2001). P2X3 expression increases in rat models of inferior alveolar nerve injury (Eriksson, Bongenhielm, Kidd, Matthews, & Fried, 1998), complete Freund's adjuvant (CFA)-induced monoarthritis (Shinoda, Ozaki, Asai, Nagamine, & Sugiura, 2005), and cast immobilisation (Sekino et al, 2014). In rat models, the number of P2X3-positive small diameter L4 and L5 dorsal root ganglion neurons increases after chronic constriction of the sciatic nerve (Novakovic et al, 1999) but decreases following axotomy (Bradbury et al, 1998).…”
mentioning
confidence: 99%